COVID-19 and Violation of Citizenship Rights in Afghanistan - Sayyid Abu al-Hassan Baqeri; Muhammad Khalil Salehi (مطالعات فقه اسلامی و مبانی حقوق, 2023)
A citizen (Persian: شهروند) is a person who is placed in a certain political society and has common citizenship with its people. Citizenship rights are the rights and obligations established by domestic law for a person, because he/she is a member of a political society and has a bilateral relationship (bilateralism) with the government. The violation of these rights is also committed by governments, since these rights are established or recognized by governments. This article, by a descriptive and analytical method, reviews the behaviors that the Afghan government has or should have done in confronting COVID-19 (Coronavirus) and which has caused violations of at least three generations of civil rights. Finally, it is clear that the right to freedom of movement, the right to access information about Coronavirus death rate (COVID-19) and the number of people infected with Corona, the right to social security and the access of patients to medicine and peripheral equipment in the fight against COVID-19have been violated in Afghanistan and even no regulations have been enacted in the country regarding the burials of Coronavirus dead bodies.